Kolaborasi Pemerintah, Swasta, dan Masyarakat dalam Peningkatan Kualitas Pelayanan Dasar di Merauke - Fonataba, Josafat (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the dynamics of collaboration between the government, private sector, and communities in improving the quality of basic services in Merauke Regency, an area with complex geographic and social challenges. Through a descriptive qualitative approach and data collection through in-depth interviews and participant observation, this study found that the collaboration model formed was hybrid, combining formal mechanisms with informal practices based on local values ​​and customary authorities. The role of non-state actors proved significant in overcoming the limitations of bureaucratic capacity, especially in the education, clean water, and basic health service sectors. These findings emphasize the importance of collaborative governance that is contextual and sensitive to local social dynamics, and broadens the scope of collaborative governance theory by including cultural and relational dimensions. The global implications of this study suggest that a community-based collaboration model can be an effective alternative in providing basic services in disadvantaged and pluralistic areas